The Physical Therapy Compact: From Development to Implementation - Leslie Adrian (International Journal of Telerehabilitation)
The Federation of State Boards of Physical Therapy (FSBPT) began the process of implementing the Physical Therapy Compact (PTC) in 2010 with a delegate assembly motion.  An interstate compact is an agreement between states to enact legislation and enter into a contract for a specific, limited purpose or to address a particular policy issue.  An interstate compact benefits patients, consumers, and licensees by addressing workforce concerns improving licensure portability from state-to-state; facilitating short-term mobility and telehealth consultation for physical therapists. FSBPT formed strategic partnerships with the American Physical Therapy Association (APTA) and Council for State Governments’ (CSG) to develop and implement the PTC.  From April 2014-present, FSBPT followed the CSG recommended stages of compact development:  Advisory, Drafting, Education, Enactment, and Transition. The enactment phase began once the threshold number of ten states required in legislation passed the compact bill in 2017.   FSBPT anticipates the compact will be fully operational and licensees will be able to take advantage of the compact by mid-2018.